Workability studies of sintered aluminium composites during hot deformation. (March 2016) - Narayan, Sumesh; Rajeshkannan, Ananthanarayanan
Experimental investigation has been carried out to evaluate the effect of titanium carbide (TiC), molybdenum carbide (Mo2 C), iron carbide (Fe3 C) and tungsten carbide (WC) addition on the composite aluminium preforms. The hot upsetting of the composite aluminium preforms with various carbide contents, namely, Al-4% TiC, Al-4% WC, Al-4% Fe3 C and Al-4% Mo2 C, and different aspect ratios, namely, 0.4 and 0.6, was carried out and the workability behaviour of the same was determined. The influence of carbide addition in the aluminium composite and initial preform geometry on the relative density ( R ), stress ratio parameters, σ θ / σ eff, σ m / σ eff andσ z / σ eff, and formability stress index was studied.